Psychological aspects of Olympic athletes` sport career termination and post-sport life - Siekanska, M.; Blecharz, J. (Studies in Sport Humanities, 2018)
The chapter is dedicated to psychological aspects linked to sport career termination by high-performance athletes, the level of which is expressed by e.g.: Olympic successes. In the fi rst part, the path of development of the interest in the transition issue occurring in the course of sport career was presented. The second part is dedicated to an overview of the most important research reports concerning the circumstances of career termination by Olympic athletes as well as the course of their further development (after professional career termination). In the last part, suggestions and recommendations on the development of competences which facilitate the process of coping during and after the termination of the last transition phase in sport career are presented.